Reliability and validity of the hand-held dynamometer “NOD”: a new instrument for assessment of isometric grip strength - Francesco Sartorio; Lorenzo Lippi; Stefano Vercelli; Federica Gallo; Davide Zanin; Sara Bergesio; Alessandro de Sire; Marco Invernizzi (BMC Musculoskeletal Disorders)
Abstract Introduction Hand grip strength (HGS) is an important measure in a physiotherapy assessment and for this purpose it is necessary to have valid and reliable instruments to measure it. In this study we aimed at investigating the reliability, validity, and agreement of the new hand-held dynamometer NOD (OT-Bioelettronica, To-Italy) compared to Jamar® hydraulic dynamometer (JD), the gold standard. Methods Fifty healthy subjects were selected; 9 trials for the dominant hand and 9 trials for the non-dominant hand were administrated to each of them: 3 trials of HGS with the JD in rung #3, 3 trials with the JD-adapted-grip (like the NOD one), and 3 trials with NOD. To verify the reliability of NOD, the Intraclass Correlation Coefficient (ICC 3,1) was calculated with a mixed effects model with the addition of adjustment variables (age, gender, dominant / non-dominant limb, trials). The model used single HGS measurements to estimate variance components, so reflecting both degree of correspondence and agreement among devices. To assess concurrent validity NOD was compared to the “gold standard” JD, in terms of ICCs and through Pearson correlation. The agreement between the methods of measurement was calculated with the Limits of Agreement (LoA) and the plots of Bland–Altman. Results All ICCs show high inter-reliability; the results are very similar for both dynamometers. The value of the adjusted ICC of NOD was 0.90. For validity, Pearson correlations of NOD towards JD and JD-adapted-grip were high (r = 0.87 and 0.88). However, the LoA and the plots of Bland–Altman demonstrated that there is no agreement between NOD and JD and between NOD and JD-adapted-grip, with NOD showing lower mean scores than JD. Conclusions NOD is a reliable and valid instrument for HGS. However, even if it cannot be considered interchangeable with JD because there is no agreement between them in free-living adults, NOD is easier to carry than other dynamometers, it has a Bluetooth® connection with a free App and it is a multi-purpose tool that should be considered both in daily practice and in clinical settings.